Management and Ecological Services of Multipurpose Agroforestry Tree Species in Ethiopia. Review - K. H. Biru; U. Cheru (Овощи России, 2025)
Relevance. Ethiopians have a long history of planting trees, and they have embraced the idea of keeping natural trees with many uses as a distinctive feature of their agricultural landscapes. Farmers use agroforestry practices to maintain a number of species of multipurpose trees. The selection of tree species, their intended benefits, and ecological services are inconsistent due to variability in agroecological conditions. The main problems with Ethiopia's multifunctional agroforestry tree species were also related to management approaches.Therefore, the purpose of this article is to examine the multipurpose agroforestry tree species in Ethiopia, their management methods, and their ecological benefits. In southern Ethiopia, Cordia africana, Millettia ferruginea, Erythrina brucei, and Olea capensis are the main multifunctional tree species used. The northern part of Ethiopia hosts Croton macrostachus, Vernonia amygdalina, Faidherbia albida, Acacia nilotica, Acacia seyal, and Grewia bicolor. The central highlands of Ethiopia are also home to Albizia gummifera, Cordia africana, Croton macrostachus, Ficus vasta, and Vernonia amygdalina. Farmers use coppicing, pollarding, and pruning tree management techniques to balance their survival with integrated crops because trees regenerate naturally. Multipurpose trees offer a range of agro-ecological services, such as improving soil fertility, mitigating erosion, mitigating the impacts of climate change, and maintaining biological diversity.